A Systematic Review on the Effectiveness of an AI-assisted Mental Health Screening and Promotion Program in Enhancing Suicide Prevention Knowledge, Attitude, and Coping Skills - Padmavathi Rali; Kakarla V. M (International Journal For Multidisciplinary Research, 2026)
AI-assisted mental health screening and promotion programs represent a promising and innovative approach to suicide prevention. Integrating these technologies with existing mental health services can strengthen prevention efforts, improve public awareness, support early intervention, and contribute to better psychological well-being and suicide prevention outcomes.